Training and Assistance in Processing Agricultural Products for the Humbahas Community - Tetty Yuliaty; M. Syafii; Hamdi; Adlina, Hafiza (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The agricultural potential in Humbang Hasundutan (Humbahas) Regency has not fully become a business that can improve the welfare of its people. Considering the pattern of farming management carried out by the community to increase their income in Humbang Hasundutan (Humbahas) Regency, in general it is still a subsystem by utilizing labor in the family with limited capital with management patterns in accordance with local wisdom. Therefore, it is necessary to provide training and assistance in the processing of agricultural products for the Humbahas community in order to be a solution to the problems that exist in the Humbahas community in optimizing natural resources and human resources to the maximum. By using survey methods, initial socialization, to training and mentoring, it is hoped that the goals of this service can be achieved. It can be seen from the success indicators, namely, partners are able to process agricultural products and are able to be creative in creating new processed products from agricultural products. The results of this service show that the maximum processing of agricultural products in the future will make the community's GRDP increase and maintain the community's economy, especially farmers in Humbang Hasundutan (HUMBAHAS).